Clinical and neuroimaging findings in MOGAD–MRI and OCT. (18th July 2021) - Bartels, Frederik; Lu, Angelo; Oertel, Frederike Cosima; Finke, Carsten; Paul, Friedemann; Chien, Claudia
Abstract: Myelin oligodendrocyte glycoprotein antibody-associated disorders (MOGAD) are rare in both children and adults, and have been recently suggested to be an autoimmune neuroinflammatory group of disorders that are different from aquaporin-4 autoantibody-associated neuromyelitis optica spectrum disorder and from classic multiple sclerosis. In-vivo imaging of the MOGAD patient central nervous system has shown some distinguishing features when evaluating magnetic resonance imaging of the brain, spinal cord and optic nerves, as well as retinal imaging using optical coherence tomography. In this review, we discuss key clinical and neuroimaging characteristics of paediatric and adult MOGAD. We describe how these imaging techniques may be used to study this group of disorders and discuss how image analysis methods have led to recent insights for consideration in future studies. Graphical Abstract: